The Green function for the Neumann boundary value problem at the semiinfinite cylinder and the flat infinite baffle - Rdzanek, Wojciech; Rdzanek, Witold; Różycka, Anna (Archives of Acoustics, 2007)
This paper presents the Green function for the Neumann boundary value problem at therigid semiinfinite cylinder and the flat rigid infinite baffle. The function has been expressed asthe combination of the Hankel functions of the first and second kinds, and their derivatives –all $n$-th order. The acoustic pressure has been presented in the two cases: the time harmonicvibrations of a sector cylinder piston located on the semiinfinite cylinder, and the annularsector piston located on the flat baffle in the vicinity of the semiinfinite cylinder.